Enhanced thermal conductivity for Ag-deposited alumina sphere/epoxy resin composites through manipulating interfacial thermal resistance. (April 2018) - Ren, Linlin; Li, Qiang; Lu, Jibao; Zeng, Xiaoliang; Sun, Rong; Wu, Jianbo; Xu, Jian-Bin; Wong, Ching-Ping
Abstract: Polymer composites with high thermal conductivity have a great potential application in modern electronics, due to their light-weight, easy process, low cost and stable physical and chemical properties. Nevertheless, most polymer composites commonly possess unsatisfactory thermal conductivity, primarily because of the high interfacial thermal resistance between inorganic fillers. Herein, we report a novel method through silver-deposition on the surface of the fillers to create a silver nanoparticle "bridge", to decrease the interfacial thermal resistance between fillers. The results demonstrate that the out-of-plane thermal conductivity of the epoxy resin/sphere alumina composites is increased to 1.304 W m −1 K −1, representing an improvement of 624% compared with pure epoxy resin. This strategy provides an insight for the design of thermally conductive polymer composites with potential to be used in next-generation electronic packaging.